2005
DOI: 10.1080/09650790500200288
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a collaborative model of action research for teacher development

Abstract: In this article the authors develop and implement a collaborative model of action research. An academic and a teacher collaborate with the purpose of improving the teaching practice and the teaching abilities of the teacher in mixed ability classes, and the collaborative ability of both academic and teacher. After a year of collaboration certain themes, related to the improvement of the teacher's practice arose. Specifically, the teacher developed a larger repertoire of teaching techniques and began to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moreover, many action research studies were conducted in one action research cycle with several improvements (Erginel, 2006;Angelides, Evangelou & Leigh, 2005, Akçay, 2009.…”
Section: Overall Research Designmentioning
confidence: 99%
“…Moreover, many action research studies were conducted in one action research cycle with several improvements (Erginel, 2006;Angelides, Evangelou & Leigh, 2005, Akçay, 2009.…”
Section: Overall Research Designmentioning
confidence: 99%
“…Action research in school can actually be performed: a) by an individual teacher (individual action research), b) by a group of teachers in collaboration with a researcher or a member of a University (collaborative action research) [1,2,6,24] or c) in a broad form by members of a University in collaboration with schools (school wide action research) [30]. It is used for the development of the curriculum, the professional development, the change of the teaching practices and the development of cooperation within schools [9,10,23].…”
Section: Models Of Teachers' Professional Developmentmentioning
confidence: 99%
“…In Cyprus, collaborative action research was developed with a teacher who aimed to be improved in classes with different learning abilities [2]. The results showed that the benefits were double, as the teacher improved teaching practices and the researcher had the experience of the facilitator.…”
Section: Models Of Teachers' Professional Developmentmentioning
confidence: 99%